Screening for tannin degradation by rumen and faecal samples of wild and domestic animals in Ethiopia - Ephraim, E.; Odenyo, A.A.; Ashenafi, M. (Springer, 2005)
Tannins limit the use of fodder trees as feed for ruminants. Removal of the effects of tannins would thus improve the nutritional quality of these trees. This prompted the study to evaluate the effect of rumen or faecal mixed cultures from different animals on tannin degradation. Tannin extracts, tannic acid and gallic acid were used to enrich media to assess if rumen or faecal mixed cultures could degrade the phenolic compounds. Rumen fluid of Acacia-adapted sheep, sheep fed on wheat bran, bush duikers (Sylvicapra grimmia) and goats fed on Leucaena pallida and Sesbania goetzei were separately inoculated into Growth Study Medium (GSM) and incubated for 5-15 days. Faecal samples from dikdik (Madoqua guentheri), camel (Camelus dromedarius), zebra (Equus quagga), Grant’s gazelle (Gazella granti) and hartebeest (Alcelaphus buselaphus) were also separately inoculated into GSM media and incubated from 3-5 days. TLC results showed that mixed cultures from rumen fluids of Acacia-adapted sheep, sheep on wheat bran, goats on Leucaena pallida and Sesbania goetzei partially hydrolysed tannic acid to pyrogallol. Complete degradation of the heterocyclic ring in tannic acid and gallic acid was achieved by the mixed cultures from the faecal samples of dikdik and this was confirmed by HPLC. Mixed cultures from faecal samples of camel hydrolysed gallic acid to phloroglucinol. This study has demonstrated that faecal microorganisms of Ethiopian dikdik could completely degrade hydrolysable tannin.